PENGALAMAN ORGANISASI, EVALUASI TERHADAP KINERJA DAN HASIL KARIR PADA KANTOR AKUNTAN PUBLIK: PENGUJIAN PENGARUH GENDER - Yeni Kuntari; Indra Wijaya Kusuma (Faculty of Economics and Business, Universitas Gadjah Mada, 2001)
During the last few years, there has been an increase in the number of women working in the field of accounting, specifically working as a public accountant. As a consequence, there has been an increasing gender issue in career opportunity, pro-fession accountability, performance evaluation, conpensation, and career promotion. Having the interesting development of the gender issue, this research has two objectives. Firstly, this research will observe the effect of gender difference to the organizational experience, performance evaluation, and career outcomes in accounting firm. Secondly, this research will observe the relationship between variable of organizational experience and variable of performance evaluation, and also relation-ship between variable of performance evaluation and the variable of career outcomes. The samples of this research are auditors and supervisors working in major accounting firm. The test of hypothesis will use Analysis of variance and correlation. The result of the research shows that in term of organizational experience, performance evaluation and career outcomes, there is no significant difference between male auditor and female auditor. The research test indicates that there is a positive correlation between variable of organizational experience and variable of performance evaluation, and also between variabel of performance evaluation and variable of career outcomes.Keywords: gender, kepuasan kerja, akuntan publik, pengalaman organisasi, hasil karir.